Questionnaire Study to Investigate the Preferences of Children, Parents, and Healthcare Professionals for Different Formulations of Oral Medicinal Products - Manfred Wargenau; Felicitas Baase; Kristin Eckardt; Lucas-Sebastian Spitzhorn; Sibylle Reidemeister; Ingrid Klingmann; Viviane Klingmann (MDPI AG, 2024)
Since the acceptability of a medicine can significantly impact therapeutic outcomes, this study aimed to determine and compare the preferences of children, parents, and healthcare professionals for the most commonly used pediatric oral medicine formulations (syrup, mini-tablets, oblong tablets, round tablets) addressing all pediatric age groups, 0-<18 years (y). This survey study employed sex-, age-, and participant group-adapted questionnaires for eight cohorts of participants, i.e., children 6-<12 y, adolescents 12-<18 y, parents of children in four age groups (0-<2 y, 2-<6 y, 6-<12 y, and 12-<18 y), nurses, and pediatricians. Descriptive statistics were used for data analysis. In the age groups 0-<2 y and 2-<6 y, mini-tablets were preferred over syrup by all participants. In the age group 6-12 y, solid dosage forms were also preferred over syrup by all participants. In the age group 12-<18 y, healthcare professionals preferred solid dosage forms over syrup. Parents preferred higher amounts of mini-tablets and syrup compared to round and oblong tablets, while adolescents' preferences did not differentiate between these formulations. Based on the study results and in contrast to current practice, it is suggested to consider solid dosage forms for future age-appropriate medicinal products already for younger age groups.